2013
DOI: 10.1145/2447976.2447993
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration with a robotic scrub nurse

Abstract: Surgeons use hand gestures and/or voice commands without interrupting the natural flow of a procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…It is stated that communication between nurse and surgeon is important during robotic surgery. It is known that most preventable errors that compromise patient safety are due to lack of team communication . The best results for the patient and for the patient's safety can be ensured by the establishment of an effective robotic surgery team .…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that communication between nurse and surgeon is important during robotic surgery. It is known that most preventable errors that compromise patient safety are due to lack of team communication . The best results for the patient and for the patient's safety can be ensured by the establishment of an effective robotic surgery team .…”
Section: Discussionmentioning
confidence: 99%
“…However, the nurses also reported a low mean of 3.3 (SD = 0.11) when it came to protecting the privacy of patients (Ohashi et al, ). When Jacob, Li, Akingba, and Wachs () carried out test‐site experiments with multimodal robotic scrub nurses, who assisted surgeons by passing and retrieving surgical instruments during simple procedures, they found that the robots recognized 95.96% of the 1000 instructions that were recorded. The robot also showed 100% accuracy when picking up instruments and 92.38% accuracy for placing instruments down accurately after use.…”
Section: Resultsmentioning
confidence: 99%
“…New methods for developing how nurses work are needed and, in the near future, the use of robots and automated device will change the content of nursing, nurses' tasks (Baril et al, ; Otero et al, ; vonHofen et al, ), and the time used for those tasks (Ohashi et al, ). For example, robots have been reported to support surgical performance targets, by reducing the lengths of operations, providing greater accuracy, and decreasing patients' risk than have traditional surgery that was performed by humans (Jacob et al, ). Thus, the use of robots to perform tasks also gives rise to ethical questions.…”
Section: Discussionmentioning
confidence: 99%
“…Jacob et al [4] proposed a technique to collaborate with a robotic scrub nurse which allow surgeons use hand gestures and/or voice commands without interrupting the natural flow of a procedure to command rot hand to passes instruments, sutures, and sponges during surgery. …”
Section: Related Workmentioning
confidence: 99%